2021
DOI: 10.1039/d0ra07868a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapor deposition and temperature-dependent Raman characterization of two-dimensional vanadium ditelluride

Abstract: Two-dimensional vanadium ditelluride has been synthesized on mica, sapphire, and h-BN substrates by atmospheric pressure chemical vapor deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Bulk VTe 2 presents a monoclinic distorted 1T' phase below 207 • C [24,25] but recently it has been shown that an undistorted hexagonal 1T structure appears upon a reduction of the thickness [18]. Lattice distortions related to thickness, temperature, and electrical field have led to quantum phases such as charge density waves (CDWs) phases [26,27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bulk VTe 2 presents a monoclinic distorted 1T' phase below 207 • C [24,25] but recently it has been shown that an undistorted hexagonal 1T structure appears upon a reduction of the thickness [18]. Lattice distortions related to thickness, temperature, and electrical field have led to quantum phases such as charge density waves (CDWs) phases [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…The 1T structure is composed of one layer of hexagonally arranged vanadium atoms sandwiched between two layers of tellurium atoms in an octahedral configuration, stacked together by weak van der Waals forces (Figure 1a). In a trigonal layered structure, 1T-VTe 2 crystallizes in the space group P-3m1 with hexagonal lattice parameters of a = b = 3.64 Å and c = 6.51 Å [24,28,29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation